2018
DOI: 10.1186/s40781-018-0185-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of nano zinc oxide (nZnO) on mitigation of gaseous emissions

Abstract: BackgroundEnteric methane (CH4) accounts for about 70% of total CH4 emissions from the ruminant animals. Researchers are exploring ways to mitigate enteric CH4 emissions from ruminants. Recently, nano zinc oxide (nZnO) has shown potential in reducing CH4 and hydrogen sulfide (H2S) production from the liquid manure under anaerobic storage conditions. Four different levels of nZnO and two types of feed were mixed with rumen fluid to investigate the efficacy of nZnO in mitigating gaseous production.MethodsAll exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
2
13
3
Order By: Relevance
“…Contrary to the present study, Sarker et al [1] reported a decreased in vitro total VFA concentration by inclusion of nano-ZnO in the diet compared with the control treatment. They noted that high levels of nano-ZnO may sometimes kill higher amounts of methanogenic bacteria, which results in a greater amount of unconverted total VFA [1]. Swain et al [54], however, showed that feeding goats with different levels of nano-ZnO instead of ZnO failed to change individual and total rumen VFA.…”
Section: Ph Ammonia-n Vfa and Protozoacontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the present study, Sarker et al [1] reported a decreased in vitro total VFA concentration by inclusion of nano-ZnO in the diet compared with the control treatment. They noted that high levels of nano-ZnO may sometimes kill higher amounts of methanogenic bacteria, which results in a greater amount of unconverted total VFA [1]. Swain et al [54], however, showed that feeding goats with different levels of nano-ZnO instead of ZnO failed to change individual and total rumen VFA.…”
Section: Ph Ammonia-n Vfa and Protozoacontrasting
confidence: 99%
“…
IntroductionMethane released during ruminal fermentation plays an important role in global warming [1,2]. One of the aims in ruminant nutrition is to reduce the release of methane from the rumen, without adverse effects on digestibility, animal health, and productivity [3].
…”
mentioning
confidence: 99%
“…Reductions in CH 4 production caused by nano or natural forms confirmed the anti-methanogenic activity of zeolite in this study. Zeolite may act as an alkalinizer and has a high capacity for H+ exchange at different pH ranges [ 34 , 35 ]. Therefore, zeolite can reduce CH 4 emission by affecting rumen H+ exchange capacity and can also affect all the end fermentation characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Hassan et al [24] indicate that the addition of nanozinc at dose 20 mg/kg feed led to reduced methane production and improved level of antioxidants. This positive effect of nanoparticles by reducing the level of methane gas can be attributed to reducing the numbers of bacteria producing it or re-directing the hydrogen flow to bind to the receptors for producing propionate [25]. The positive effect of these minerals also lies in their improvement of some digestive enzymes in the alimentary channel [26].…”
Section: The Function Of Nanocompoundsin the Ruminal Fermentationmentioning
confidence: 99%